1994
DOI: 10.1143/jjap.33.l312
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting Properties of Ultrathin Films of YBa2Cu3Ox Prepared by Metalorganic Chemical Vapor Deposition at 500°C

Abstract: Low-temperature ( 500°C) growth of YBa2Cu3O x films by metaloganic chemical vapor deposition on (100)MgO substrates using N2O as an oxidizing agent has been investigated. Films 12 unit cells thick show superconducting onset critical temperature of 89 K and zero-resistivity critical temperature of 80 K. Films 4 unit cells thick show T c (zero) of 30 K. Films as thin as 3 unit cells thick reveal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 12 publications
0
4
1
Order By: Relevance
“…Although we obtained by the MOMBE c-axis thin films at lower growth temperatures than, e.g., for MOCVD growth using [1], the use of or in MOMBE has not produced any distinct changes in the growth and quality of the c-axis films. This is in contradiction with Zama et al [5] promoting the idea that the source precursor is the origin of record low temperature growth of 500 when using the same precursors. But, the growth technique and growth conditions were different from ours.…”
Section: Resultscontrasting
confidence: 69%
See 2 more Smart Citations
“…Although we obtained by the MOMBE c-axis thin films at lower growth temperatures than, e.g., for MOCVD growth using [1], the use of or in MOMBE has not produced any distinct changes in the growth and quality of the c-axis films. This is in contradiction with Zama et al [5] promoting the idea that the source precursor is the origin of record low temperature growth of 500 when using the same precursors. But, the growth technique and growth conditions were different from ours.…”
Section: Resultscontrasting
confidence: 69%
“…In the literature, growth of Y-Ba-Cu-O is performed at temperatures as low as 400-600 for c-axis oriented thin films, but as noted in the review by Leskala et al [4] these films are usually not superconducting and requires post-annealing at high temperatures (usually above 750 ). However, Zama et al [5] obtained c-axis (Y123) superconducting thin films for a growth temperature of 500 using MOCVD deposition in a atmosphere and subsequent post-annealing in at 400 . The authors indicated that they took advantage of the supposed enhanced surface migration of the MO source precursors at low growth temperatures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The problem is that the vaporization temperature is very close to the decomposition temperature of the precursors. [24] Oligomer formation was prevented by adducts, and decomposition was minimized by using a reduced vaporization temperature. In order to prevent oligomer formation, both the use of adducts, and water-free synthesis of the precursor, have been proposed and demonstrated.…”
Section: Design Of Metal±organic Precursorsmentioning
confidence: 99%
“…[6]) reveals that a deposition temperature of at least 700~ is generally needed to obtain the superconducting YBa2Cu307_ x phase in situ. A recent paper has even reported MOCVD of superconducting films at as low temperature as 500~ using N20 [11]. First, it has been observed that by using plasma-activated CVD, the superconducting compound can be obtained at a lower temperature.…”
Section: Introductionmentioning
confidence: 99%